2021
DOI: 10.3390/cancers13102423
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer (BC) Is a Window of Opportunity for Smoking Cessation: Results of a Retrospective Analysis of 1234 BC Survivors in Follow-Up Consultation

Abstract: Breast cancer (BC) is the most commonly diagnosed type of cancer and the leading cause of cancer deaths in women. Smoking is the principal modifiable risk factor for cancers and has a negative influence on long-term survival. We conducted a retrospective study on consecutive BC survivors seen at follow-up consultations between 3 June and 30 October 2019 at Institut Curie, Paris, France. Smoking behaviors were evaluated prospectively via interviewer-administered questionnaires. The aim of this study was to desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…(179). Tobacco smoking represents one of the important risk factors for breast cancer (180)(181)(182). Smoking not only affects the DNA methylation pattern of breast tumors, but it has been a critical factor linking DNA methylation and breast cancer for ER positive cancer subtypes (183,184).…”
Section: Figurementioning
confidence: 99%
“…(179). Tobacco smoking represents one of the important risk factors for breast cancer (180)(181)(182). Smoking not only affects the DNA methylation pattern of breast tumors, but it has been a critical factor linking DNA methylation and breast cancer for ER positive cancer subtypes (183,184).…”
Section: Figurementioning
confidence: 99%
“…Breast cancer caused 685,000 deaths in 2020, and it became the fifth leading cause of cancer mortality worldwide. It has been confirmed that cigarette smoking, one of the most important environmental risk factors, represents a significant effect on breast cancer risk ( 1 4 ).…”
Section: Introductionmentioning
confidence: 99%